PRINCIPLES OF OPERATION OF THE ELECTORAL SYSTEM AS A CONSENSUS FACTOR IN A SPLIT SOCIETY - Попков, Д. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The article deals with the mechanism of functioning of the electoral system from the point of view of its perception as an institution for consolidating a split society. Attention is focused on the need to ensure consensus not only at the stage of political decision-making by the representative authorities, but also at the previous stage of their formation. The importance of the aspect of the consolidating bundling of legislatures for the stabilization of society is shown with the help of an interdisciplinary analogy of the principles of assessing the acceptability of the functioning of the judiciary according to established international practice.